Design and Finite Element Analysis of New Superconducting Maglev Bogie - Wu CHEN; Bin DENG; Zigang DENG; Wenbiao HUO; Zhihui YIN (机车电传动)
Aiming at inconsistent problem with the actual working condition when the boundary condition of the suspended surface was set to the whole constraint in the finite element analysis of the maglev train bogie, a new method with the boundary constraint of elastic support and on the purpose of lightweight train was brought out. A new magnetic levitation bogie of high temperature superconducting was designed by SolidWorks software, and according to the different operating conditions of the maglev train, the overall strength of the bogie and the minimum spacing between the Dewar beam and the track were analyzed. The results showed that the bogie met the design requirements and provided the basis for the subsequent optimization calculation.